Paleogeographic modulation of Phanerozoic climate by albedo compensation of interhemispheric land imbalances - G. Muttoni; D.V. Kent (Earth-Science Reviews, 2026)

A geoarchaeological review of Balzi Rossi, Italy: A crossroad of Palaeolithic populations in the northwest Mediterranean - D.D. Ryan; E. Starnini; M. Serradimigni; E. Rossoni-Notter; O. Notter; A. Zerboni; F. Negrino; S. Grimaldi; M. Vacchi; L. Ragaini; A. Rovere; A. Perego; et al. (Quaternary Science Reviews, 2024)

Deformation capacity evaluation for flat slab seismic design - A. Muttoni; D. Coronelli; M. Lamperti Tornaghi; L. Martinelli; I. R. Pascu; A. Pinho Ramos; G. Tsionis; P. Bamonte; B. Isufi; A. Setiawan (Bulletin of Earthquake Engineering, 2022)
In flat-slab frames, which are typically designed as secondary seismic structures, the shear failure of the slab around the column (punching failure) is typically the governing failure mode which limits the deformation capacity and can potentially lead to a progressive collapse of the structure. Existing rules to predict the capacity of flat slab frames to resist imposed lateral displacements without losing the capability to bear gravity loads have been derived empirically from the results of cyclic tests on thin members. These rules account explicitly only for the ratio between acting gravity loads and resistance against concentric punching shear (so-called Gravity Shear Ratio). Recent rational models to estimate the deformation capacity of flat slabs show that other parameters can play a major role and predict a significant size effect (reduced deformation for thick slabs). In this paper, a closed-form expression to predict the deformation capacity of internal slab-column connections as a function of the main parameters is derived from the same model that has been used to develop the punching shear formulae for the second generation of Eurocode 2 for concrete structures. This expression is compared to an existing database of isolated internal slab-column connections showing fine accuracy and allowing to resolve the shortcomings of existing rules. In addition, the results of a testing programme on a full-scale flat-slab frame with two stories and 12 columns are described. The differences between measured interstorey drifts and local slab rotations influencing their capacity to resist shear forces are presented and discussed. With respect to the observed deformation capacities, similar values are obtained as in the isolated specimens and the predictions are confirmed for the internal columns, but significant differences are observed between internal, edge and corner slab-column connections. The effects of punching shear reinforcement and of integrity reinforcement (required according to Eurocode 2 to prevent progressive collapse after punching) are also discussed.